INFLUENCE ANALYSIS OF MUDHARABAH FINANCING AND QARDH FINANCING TO THE PROFITABILITY OF ISLAMIC BANKING IN INDONESIA - Taudlikhul Afkar (Asian Journal of Innovation and Entrepreneurship, 2017)
The purpose of this study is to determine the effect of mudharabah financing and qardh financing on the profitability of Islamic Banking in Indonesia. The research approach used is descriptive quantitative. Sampling by purposive sampling with period 2010-2014 data from financial statements of Islamic Banking. Multiple linear regression is used as an analytical tools. The results showed that mudharabah financing did not significantly affect the profitability of Islamic Banking. While qardh financing has a significant effect on the profitability of Islamic Banking in Indonesia. The finding in this research is the absence of influence of mudharabah financing on syariah bank perofitabilitas so it gives picture that mudharabah financing does not give positive impact to profitability of syariah bank in Indonesia.Â